WOMENâ€™S LANGUAGE FEATURES IN â€œDORA AND THE LOST CITY OF GOLDâ€ MOVIE SCRIPT - Ella Apriyanti (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2018)
This research discusses the women’s language features used in Dora and the Lost City of Gold movie script. This research aims to find out the features of women’s language style in the Dora and the Lost City of Gold movie script. The research methodology used in this study is a qualitative descriptive method. The data of this research is taken from the Dora and the lost city of gold movie script. To collect data, the researcher used several steps: downloading, reading movie script, watching movie repeatedly, selecting and coding conversations containing women’s language features in Dora and the Lost City of Gold movie script. The result of the research show that not all types of women’s language features were used by the characters of Dora and the Lost City of Gold movie script. The women character used five types of women’s language features, namely lexical hedges or filler 5 data, tag question 2 data, rising intonation on declaratives 1 data, intensifiers 5 data and emphatic stress 1 data. Meanwhile, men’s characters used only three types, they were lexical hedges 3 data, intensifiers 1 data, and emphatic stress 1 data. The features that were not used by the characters, they were empty adjectives, precise color terms, avoidance of strong swear words, hypercorrect grammar, and superpolite form. Based on the comparison of women’s and men’s characters could be found that women used women’s language features much more than men’s characters.